What You Should Know about Your School's Concussion Policy: Column Editor: K. Andrew R. Richards. (2nd September 2016) - Potteiger, Adam J.; Wright, Paul M.
Abstract : The purpose of this article is to inform physical educators, coaches and administrators of the common features and variation between concussion policies among states, which will help them advocate for the health and safety of their students.